2021
DOI: 10.3390/rs13214381
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Urban Floods Based on a SWMM-MIKE21-Coupled Model Using GF-2 Data

Abstract: Global climate change and rapid urbanization have caused increases in urban floods. Urban flood risk assessment is a vital method for preventing and controlling such disasters. This paper takes the central region of Cangzhou city in Hebei Province as an example. Detailed topographical information, such as the buildings and roads in the study area, was extracted from GF-2 data. By coupling the two models, the SWMM and MIKE21, the spatial distribution of the inundation region, and the water depth in the study ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This is consistent with previous studies that have found that increasing the size of LID facilities can reduce peak runoff flows [ 54 ]. Wang [ 55 ] and Zhao [ 56 ] et al found that the maximum flow rates in most urban areas were small. The possibility of flow velocity loss before and after construction is small.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous studies that have found that increasing the size of LID facilities can reduce peak runoff flows [ 54 ]. Wang [ 55 ] and Zhao [ 56 ] et al found that the maximum flow rates in most urban areas were small. The possibility of flow velocity loss before and after construction is small.…”
Section: Discussionmentioning
confidence: 99%
“…To create a basis for mitigating the negative impacts of flooding in Metro Residential Area, this research is conducted to apply GIS and SWMM model to assess urban flooding in this residential area. The application of SWMM model in urban flooding research has been IOP Publishing doi:10.1088/1755-1315/1170/1/012007 2 used in many areas around the world and has yielded many practical results, providing good support for urban drainage management [3][4][5]. In Vietnam, the use of SWMM model to assess urban flooding is also quite popular in many localities in the current period [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Chinh et al [22] used multivariate statistical analysis to analyse the flood loss of residential buildings in Cantor city in the Mekong Delta. Zhao et al [23] used the coupling of the SWMM and MIKE 21 model to analyse the flood inundation loss in the central area of Cangzhou, Hebei. Guo et al [24] created a flood risk assessment model of flood storage and detention area based on a mechanical process to quantitatively evaluate the flood risk level of flood storage and detention area during the commissioning of flood diversion and storage project.…”
Section: Introductionmentioning
confidence: 99%